Benthic grazing in a eutrophic river: cascading effects of zoobenthivorous fish mask direct effects of herbivorous fish - Gerke, Madlen; Cob Chaves, Daniel; Richter, Marc; Mewes, Daniela; Schneider, Jörg; Hübner, Dirk; Winkelmann, Carola (PeerJ, 2018)
Benthic grazing strongly controls periphyton biomass. The question therefore arises whether benthic grazing could be used as a tool to reduce excessive growth of periphyton in nutrient-enriched rivers. Although benthic invertebrate grazers reduce the growth of periphyton, this is highly context dependent. Here we assessed whether the only obligate herbivorous fish in European rivers, the common nase (Chondrostoma nasus L.), is able to reduce periphyton biomass in a eutrophic river. We conducted three consecutive in situ experiments at low, intermediate and high densities of nase in the river using standard tiles on the river bottom naturally covered with periphyton that were accessible to fish and tiles that excluded fish foraging with electric exclosures. The biomass of benthic invertebrate grazers was very low relative to nase. We hypothesised that nase would reduce periphyton biomass on accessible tiles and therefore expected higher periphyton biomass on the exclosure tiles, at least at intermediate and high densities of nase in the river. Contrary to our expectation, the impact of fish grazing was low even at high fish density, as judged by the significantly lower chlorophyll a concentration on exclosure tiles even though the ash-free dry mass on accessible and exclosure tiles did not differ. The lower chlorophyll a concentrations on exclosure tiles might be explained by a higher biomass of invertebrate grazers on the exclosure tiles, which would indicate that the effect of invertebrate grazers was stronger than that of herbivorous fish grazers. The high biomass of invertebrate grazers on exclosure tiles likely arose from the exclusion of zoobenthivorous fish, which occur in the river at high densities. The results of our small-scale experiments suggested that cascading top-down effects of zoobenthivorous fish have a higher impact on periphyton biomass than direct effects of herbivorous nase.
Keywords: Top-down control; Benthic grazing; Eutrophication; Trophic cascades; Indirect interactions; Periphyton; Fish